Efficacy and safety of tirofiban therapy in patients receiving endovascular treatment after large vessel ischaemic stroke: A systematic review and meta-analysis. (October 2020) - Zhang, Pengfei; Guo, Yanting; Shen, Jie; Li, Hongbin; Wang, Ruixian; Wang, Ying; Yu, Xiaojie; Yao, Qingping
Highlights: Tirofiban administration in endovascular treatment significantly improved the 3-month favourable functional outcome. Tirofiban combined with endovascular treatment increases the risk of fatal intracranial haemorrhage after large artery occlusion, whereas tirofiban does not increase the risk of other bleeding complications. With the inclusion of four recent studies, this meta-analysis produced more comprehensive and precise estimates than previous studies and can provide guidance for the clinical application of tirofiban. Abstract: Background: Although tirofiban therapy is considered a potentially effective treatment to reduce the incidence of thrombotic complications in patients receiving endovascular treatment (EVT), the safety and efficacy of tirofiban remain controversial. Our objective was to investigate the efficacy and safety of EVT plus tirofiban therapy in patients with emergent large artery occlusion. Methods: Relevant articles from randomized controlled trials (RCTs) or observational studies that compared treatment with tirofiban to treatment without tirofiban in patients undergoing EVT were retrieved from the PubMed and Embase databases. We calculated odds ratios (ORs) with corresponding 95% confidence intervals (CIs) for the safety and efficacy outcomes based on a random effects model. Results: Twelve studies including 2533 patients were identified for the analysis. Overall, the risk of fatal intracranial haemorrhage (ICH) was higher for the treatment with tirofiban group than for the treatment without tirofiban group in patients with large artery occlusion who underwent EVT ( p = 0.002), whereas the risk of any ICH, symptomatic ICH, parenchymal haematoma type 2, in-hospital mortality and 3-month mortality did not differ significantly ( p > 0.05). No significant differences in reocclusion rate, recanalization rate or excellent functional outcome were found between the patients treated with or without tirofiban, but significantly favourable functional outcome at 3 months occurred in the tirofiban group ( p = 0.017). Conclusions: Tirofiban administration in patients receiving EVT significantly improved 3-month favourable functional outcomes, whereas an increased risk of fatal ICH was also observed. Further rigorous trials are needed to verify the safety of tirofiban.